Whole genome sequencing identifies loci specifically associated with thoracic aortic wall defects and abdominal aortic aneurysms in patients with European ancestry - Grace H. Miner, PhD; Alan E. Renton, PhD; Ella Taubenfeld, BS; Rami O. Tadros, MD; Edoardo Marcora, PhD; Robert A. Lookstein, MD; Peter L. Faries, MD; Michael L. Marin, MD (JVS - Vascular Science, 2020)
Objective: The objective of this study was to better understand the pathophysiology and underlying genetic mechanisms behind two abdominal aortic aneurysm (AAA) subtypes using computed tomographic imaging in combination with whole genome sequencing. Methods: Patients with a known AAA and European ancestry were included in this investigation and underwent genetic and image analysis. Patients with AAAs and indications of descending thoracic aortic pathology (aortic dissection, penetrating aortic ulcers, intramural hematoma, atheromas, ulcerative plaque, and intramural ulceration, and intimal flaps/tears) were classified as having thoracic aortic disease, grouped together, and compared with patients with an AAA and a normal descending thoracic aorta. Whole genome sequencing was then performed on the 93 patients who had imaging features consistent with thoracic aortic disease and the 126 patients with a normal descending thoracic aorta. Results: The results of this study suggest one variant-level, four gene-level, and one gene set-level associations in patients with thoracic aortic disease who also had an AAA. The variant rs79508780 located in TSEN54 achieved study-wide significance (P = 1.71E-06). BATF3 and SMLR1 were significantly associated and EFCAB3 and TAF4 were reached suggestive assocation with a diseased descending thoracic aorta (P = 5.23E-26, P = 1.86E-25, P = 1.54E-05, and P = 8.31E-05, respectively). Gene sets were also compiled using MSigDB and trait-based index single nucleotide variation from major genome-wide association studies. GO_DNA_DOUBLE_STRAND_BREAK_PROCESSING, a gene set related to double-stranded DNA break repair, was significantly associated with thoracic aortic disease in AAA patients (P = 1.80E-06). Conclusions: This pilot study provides further evidence that an AAA may be the end result of multiple degenerative pathways. Genetic variations in vitamin D signaling, cholesterol metabolism, extracellular matrix breakdown, and double-stranded DNA break repair pathways were associated with European patients who had an AAA and thoracic aortic disease. Additionally, this study provides support for the application of a radiogenomic approach for the investigation of other potential pathologies that could lead to the development of an AAA or influence future management decisions. (JVS–Vascular Science.) Clinical Relevance: In this study, we provide evidence that abdominal aortic aneurysms (AAAs) may be a result of multiple pathophysiologies rather than a single disease. We have identified genetic variants involved in vitamin D signaling, cholesterol metabolism, extracellular matrix breakdown, and double-stranded DNA break repair associated with structural defects in the aortic wall in patients with AAAs who are of European descent. Patients with AAAs and structural defects in the thoracic aorta have been previously linked to differential behavior after endovascular aneurysm repair. These patients with wall defects exhibited greater sac regression, a marker of surgical success, after endovascular aneurysm repair. Our study demonstrates the usefulness of a radiogenomic approach for elucidating mechanisms behind the formation and future behavior of AAAs that could aid surgeons in making future procedural and management decisions.